Effects of a 5-week intake of erythritol and xylitol on vascular function, abdominal fat and glucose tolerance in humans with obesity: a pilot trial - Christoph Beglinger; Henner Hanssen; Arno Schmidt-Trucksäss; Jürgen Drewe; Valentine Bordier; Fabienne Teysseire; Philipp Madörin; Oliver Bieri; Anne Christin Meyer-Gerspach; Bettina K Wölnerhanssen (BMJ Nutrition, Prevention & Health)
Introduction Previous studies in humans and rats suggest that erythritol might positively affect vascular function, xylitol decrease visceral fat mass and both substances improve glycaemic control. The objective of this study was to investigate the impact of a 5-week intake of erythritol and xylitol on vascular function, abdominal fat and blood lipids, glucose tolerance, uric acid, hepatic enzymes, creatinine, gastrointestinal tolerance and dietary patterns in humans with obesity.Methods Forty-two participants were randomised to consume either 36 g erythritol, 24 g xylitol, or no substance daily for 5 weeks. Before and after the intervention, arterial stiffness (pulse wave velocity, arteriolar-to-venular diameter ratio), abdominal fat (liver volume, liver fat percentage, visceral and subcutaneous adipose tissue, blood lipids), glucose tolerance (glucose and insulin concentrations), uric acid, hepatic enzymes, creatinine, gastrointestinal tolerance and dietary patterns were assessed. Data were analysed by linear mixed effect model.Results The 5-week intake of erythritol and xylitol showed no statistically significant effect on vascular function. Neither the time nor the treatment effects were significantly different for pulse wave velocity (time effect: p=0.079, Cohen’s D (95% CI) −0.14 (−0.54–0.25); treatment effect: p=0.792, Cohen’s D (95% CI) control versus xylitol: −0.11 (–0.61–0.35), control versus erythritol: 0.05 (0.44–0.54), erythritol versus xylitol: 0.07 (–0.41–0.54)). There was no statistically significant effect on abdominal fat, glucose tolerance, uric acid, hepatic enzymes and creatinine. Gastrointestinal tolerance was good except for a few diarrhoea-related symptoms. Participants of all groups reduced their consumption of sweetened beverages and sweets compared with preintervention.Conclusions The 5-week intake of erythritol and xylitol showed no statistically significant effects on vascular function, abdominal fat, or glucose tolerance in people with obesity.Clinical trial registration NCT02821923.